Institutionalizing problem-oriented policing: An evaluation of the EMUN reform in Israel - Weisburd, David (Criminology & public policy, 2020)
Research In 1979 Herman Goldstein proposed a radical reform—problem-oriented policing (POP)—which has had tremendous impact on scholars and practitioners. Even though his paper and subsequent work led to a large body of literature on how to carry out problem-oriented policing tactics, scholars have often ignored the question of how POP can be institutionalized in police agencies. In this article, we evaluate a reform in Israel—EMUN— that attempted to institutionalize problem-oriented policing on a national scale. Focusing on property crime, we compare three treatment stations (with high, moderate, and low crime) with control stations chosen through a systematic matching procedure. We find that there are large and significant reductions in the targeted areas (termed “polygons”) for high- and moderate-property- crime stations as compared with the control stations. We also do not find evidence of displacement but instead evidence of significant diffusions of crime control benefits. Importantly, property crime declines occurred in these stations overall. Significant benefits were not found for the low-crime treatment station. We attribute this to the low base rate of crimes and low resource allocation in this station. Policy Implications These findings suggest that the EMUN reform provides a potential model for institutionalizing problem-oriented policing as an organizational reform. EMUN attempted to support and reinforce each of the main steps of the problem-oriented policing model. It also developed sophisticated computer tools to aid in this process that not only supported problem-solving efforts but also allowed for wide-scale supervision of each stage of the POP model.